O discurso etarista sobre o sujeito feminino: efeitos de sentido da ordem do político e do ideológico mobilizados pela inscrição "#ATUALIZAPORCHAT" no ambiente digital - Silva, Elba Silveira Chagas (2023)
This research is based on the theory of French Discourse Analysis, founded by the French scholar Michel Pêcheux (1960), and its corpus was delimited from excerpts of comments on the virtual platforms Facebook and YouTube, from which the functioning of discourses related to ageism was analyzed concerning the female gender. The object of analysis was extracted from a video entitled in portuguese language “#ATUALIZAPORCHAT," posted on the aforementioned social networks as a response to another video titled "RESPONSÁVEL," which triggered a series of comments on both platforms. To expand the analytical approach, the theory of digital discourse analysis was also employed, whose assumptions are theoretical devices that aided in the processes of analytical production. The overall objective of this study is to conduct an analysis of the corpus originating in the digital universe, employing specific categories from French Discourse Analysis, while considering a post-dualistic and ecological perspective of discourse. This perspective regards technodiscursive forms as essential elements for the production and establishment of meanings pertaining to ageism concerning women that circulate in virtual space. Among the specific objectives is the understanding of the production of meaning effects in discourses about the female subject, constituted by statements on ageism, pointing out the clash of discursive formulations materialized in the virtual space, observing the operation of ideology, discursive formations, and historicity in language production. It is also intended to emphasize that the interpretations of discourses are materialized through "slippages of meaning" and that the use of paraphrase and polysemy signifies the inscription of language in history since reformulating and updating statements circulating in social environments is constitutive of discursive memory. Furthermore, the study aims to comprehend, through descriptive and analytical approaches, the movement of subjects' ideas in their positions as readers and enunciators based on the ecological perspective of discourse, with its technolinguistic dimension, integrally linked to language contexts. Finally, the goal is to destabilize the "logically stabilized universes" through the analysis of the process of signification, demonstrating that meanings are multiple and unattainable in their totality since language is open to multiple interpretations. The theoretical framework draws upon Pêcheux (2010, 2014, 2015), Paveau (2013, 2021), Orlandi's epistemology (2007, 2012, 2015, 2016), Maldidier (2003), Mazière (2017), Possenti (2018), among other scholars. Through the analysis of video excerpts and Discursive Sequences comprising the corpus are revealed, the opaque nature of language, the diverse discursive formations arising from ideological formations, and the political and material sense that drives statements about ageism, intertwining language, the subject, and history. It becomes evident that the analyzed materialities become historicized, giving rise to the revival of ideologies attempting to impose themselves amidst diverse ways of thinking and acting, provoking clashes of ideas among individuals in the social sphere, materializing discourses in the virtual space.